THE RELATIONSHIP BETWEEN ENVIRONMENTAL SANITATION AND THE INCIDENCE OF DIARRHEA INTOODDLERS - Deli Syaputri Sya Putri (JURNAL KESMAS DAN GIZI (JKG), 2022)
Diarrhea is an endemic disease with a potential incidence (KLB) and is still a cause of death in Indonesia especially in infants. Several factors increase the potential for diarrhea in infants, such as environmental factors, including the provision of clean water, waste management, toilet and sewage facilities.Tigapanah is a sub-district located in Karo District, North Sumatra, with diarrhea cases by 2021 namely the fifth rank of the top ten of the disease. The purpose of this study is to know the correlation of knowledge and environmental sanitation with the incidence of diarrhea in infants in the workplace of Puskesmas Tigapanah, Karo District this type of research is an analytic observation with a cross sectional approach. The research population is that of all mothers with toddlers in sub-district Tigapanah of Karo district. The sampling technique used is purposive sampling technique. The analysis used was the chi square test. The results of the study were concluded that three research variables were not related to the incidence of diarrhea in toddlers: the water source with P Value 0.202 , A family latrine with P value of 0.406, and a knowledge of the respondents with P Value 0,635. Three variables related to an infant's diarrhea problem are a garbage dump with a value of 0,000, and a wastewater drain with a P value of 0.003 and an action with P value 0.001. It is recommended to the public to prevent the diarrheal diseases of infants from washing their hands in runoff water and using soap before eating and afterward, repairing garbage disposal and sewer system, and maintaining sanitation.